Metabolic pathways of benzimidazole anthelmintics in harebell (Campanula rotundifolia) - Stuchlikova, Lucie; Jirásko, Robert; Skalova, Lenka; Pavlik, Frantisek; Szotakova, Barbora; Holčapek, Michal; Vanek, Tomas; Podlipna, Radka (My University, 2016)
Benzimidazoles anthelmintics, which enter into environment primarily through excretion in the feces or urine of treated animals, can affect various organisms and disrupt ecosystem balance. The present study was signed to test the phytotoxicity and biotransformation of the three benzimidazole anthelmintics albendazole (ABZ), fenbendazole (FBZ) and flubendazole (FLU) in the harebell (Campanula rotundifolia). This meadow plant commonly grows in pastures and comes into contact with anthelmintics through the excrements of treated animals. Suspensions of harebell cells in culture medium were used as an in vitro model system. ABZ, FLU and FBZ were not found to be toxic for harebell cells, which were able to metabolize ABZ, FLU and FBZ via the formation of a wide scale of metabolites. Ultrahigh-performance liquid chromatography coupled with high mass accuracy tandem mass spectrometry (UHPLC-MS/MS) led to the identification of 24, 18 and 29 metabolites of ABZ, FLU and FBZ, respectively. Several novel metabolites were identified for the first time. Based on the obtained results, the schemes of the metabolic pathways of these anthelmintics were proposed. Most of these metabolites can be considered deactivation products, but a substantial portion of them may readily be decomposed to biologically active substances which could negatively affect ecosystems.
Metabolické cesty benzimidazolových anthelmintik ve zvonku okrouhlistém (Campanula rotundifolia)
Keywords: Drug metabolism; Biotransformation; Albendazole; Flubendazole; Phytoremediation; athelmintika; metabolismus léčiv; UHPLC/MS